The accumulation of disadvantage: How motherhood and relationship breakdown influence married and single mothers' economic outcomes - Susan Harkness (University of Essex, Institute for Social and Economic Research (ISER), 2022)
This study examines how earnings penalties to motherhood combine with the cost of partner absence to affect single mothers' economic well-being. Using 25-years of longitudinal data from the Panel Study of Income Dynamics (PSID) from 1990 to 2015 and fixed-effect models with individual-specific slopes I find that, after adjusting for needs, the transition to parenthood is as strongly linked to reduced income as partner absence. Comparing how these different routes to single motherhood affect economic outcomes, I show that previously married mothers face larger income penalties than those who were single when their first child was born because they see larger declines in their own earnings following childbirth. The results illustrate how marriage and parenthood, alongside partner absence, shape the economic prospects of single mother families, and highlight the importance of reducing gender inequalities in the labor market for improving single mothers' economic well-being.
Keywords: 330; child penalties; female earnings; income; poverty; single mothers; fixed effect withindividual slopes models; life course analysis